Ointment of Brassica oleracea var. capitata Matures the Extracellular Matrix in Skin Wounds of Wistar Rats - Sarandy, Mariáurea Matias (Evid Based Complement Alternat Med, 2015)
Wound healing is a complex process that aims to restore damaged tissue. Phytotherapeutics, such as cabbage, Brassica oleracea var. capitata (Brassicaceae), and sunflower, Helianthus annuus L. (Asteraceae) oil, are used as wound healers. Five circular wounds, each 12 mm in diameter, were made in the dorsolateral region of each rat. The animals were divided into four groups: balsam (B. oleracea); ointment (B. oleracea); sunflower oil (Helianthus annuus); control (saline solution 0.9%). These products were applied daily for 20 days and every four days the tissues of different wounds were removed. The wound contraction area, total collagen, types I and III collagen, glycosaminoglycans, and tissue cellularity were analyzed. In the groups that received ointment and balsam there was reduction in the wound area on days 4, 8, 12, and 20. Throughout the trial period, the balsam and ointment groups showed a higher amount of total collagen, type I collagen, and glycosaminoglycan compared to the others groups. The rats in the groups treated with B. oleracea var. capitata showed a higher number of cells on days 8, 16, and 20. B. oleracea was effective in stimulating the maturation of collagen and increasing the cellularity, as also in improving the mechanical resistance of the newly formed tissue.